ANÁLISE DA ESTRUTURA POPULACIONAL DE Drosophila ornatifrons (DIPTERA: DROSOPHILIDAE) COLETADAS NA REGIÃO SUL DO BRASIL - Zorzato, Samara Videira (2015)
Drosophila ornatifrons belongs to the Neotropical guarani group of Drosophila. In Brazil, this species can be found mainly in remnants of different phytophysiognomies of the Atlantic Forest. Despite recent studies have started to analyze species of the guarani group, the examination of population structure and how the diversity is distribute in forest fragments has not been their main goal. Thus, the objective of this work was to access allozyme and microsatellite variation in five natural populations of D. ornatifrons from southern Brazil, in order to contribute to better understand the pattern of genetic variability distribution for this species. We analyzed nine allozyme loci, six polymorphic, and 10 polymorphic microsatellite loci, totaling 129 individuals sampled. A high genetic diversity (Ho) was observed for both markers when compared to other Drosophila species, especially in a population of a conservation park (SSF) located in Guarapuava/PR (Ho = 0.5330 and 0.4067 - allozyme and microsatellite, respectively) and in a population of an area located close to the coast of Rio Grande do Sul state (CAN - Ho = 0.4153 and 0.4050). Only the microsatellite loci showed high heterozygote deficiency (Fis = 0.3734), and moderate genetic differentiation was detected for both markers (Fst = 0.0737 - allozyme; Fst = 0.0796 - microsatellite), despite higher genetic distances were detected for microsatellite. The bottleneck test resulted positive for three of the five analyzed populations (SSF e CAN - microsatellite and allozyme, and Parque Municipal das Araucárias - allozyme). No association between geographic and genetic distances was detected (p = 0.8220 and 0.8390 - Mantel test for allozyme and microsatellite, respectively), however, only the Neighbor Joining dendogram for allozymes separated the populations of the Paraná state from the others. The high diversity found in SSF and CAN could be due to a recent bottleneck and/or because of the historical/ecological features of these areas that favored the maintenance of their high diversity. The moderate genetic differentiation, associated with the absence of correlation with geographic distance, could be a result of the maintanence of ancestral polymorphism and/or genetic drift, probably due to the restrict capacity of dispersion of these insects, and to the isolation and great distance among the fragments of Atlantic forest sampled.